KINERJA PENGELOLA PUSAT KEGIATAN BELAJAR MASYARAKAT (PKBM) MITRA RIAU JAYA CEMERLANG KECAMATAN MARPOYAN DAMAI KOTA PEKANBARU - Ricka Anggraini Anggraini; Sumardi '; Jaspar Jas Jas (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract:The manager of community learning centre (PKBM) has five duties in applying study program in PKBM. They are to identify society needed learning, plan the program application that appropriate with society needed, guide the program application, has evaluation to the program that goes on, and report the program application. But, it has been found the problem at application of manager duties in PKBM Mitra Riau Jaya Cemerlang is not proper about the application of the five duties PKBM manager.It is qualitative research to know more the problem of PKBM manager roles in PKBM Mitra Riau Jaya Cemerlang, Marpoyan Damai district, Pekanbaru. This research is done on February to September 2014. The data collecting techniques in this research are observation, interview and documentation. The subjective of this research consist of two core informants: chairman and secretary of PKBM Mitra Jaya Cemerlang and two control informants: guidance and tutor of PKBM Mitra Riau Jaya Cemerlang.The research findings show the effect of low manager roles PKBM Mitra Riau Jaya Cemerlang is not understanding manager about technique to identify society needed, not to plan of study program in PKBM, lack of understanding in guiding tutor in order that study program is going well, not evaluate the study program, and not understand to report the study program that goes on. To do the PKBM manager duties properly, it is suggested by the manager to get training about PKBM duties manager from educational service out of school. dinas pendidikan luar sekolah. Key Words : Performance, PKBM